Visual target selection and motor planning define attentional enhancement at perceptual processing stages - Collins, Therese; Heed, Tobias; Röder, Brigitte (Frontiers in Human Neuroscience, 2010)
Extracting information from the visual field can be achieved by covertly orienting attention to different regions, or by making saccades to bring areas of interest onto the fovea. While much research has shown a link between covert attention and saccade preparation, the nature of that link remains a matter of dispute. Covert presaccadic orienting could result from target selection or from planning a motor act toward an object. We examined the contribution of visual target selection and motor preparation to attentional orienting in humans by dissociating these two habitually aligned processes with saccadic adaptation. Adaptation introduces a discrepancy between the visual target evoking a saccade and the motor metrics of that saccade, which, unbeknownst to the participant, brings the eyes to a different spatial location. We examined attentional orienting by recording event-related potentials (ERPs) to task-irrelevant visual probes flashed during saccade preparation at four equidistant locations including the visual target location and the upcoming motor endpoint. ERPs as early as 130–170 ms post-probe were modulated by attention at both the visual target and motor endpoint locations. These results indicate that both target selection and motor preparation determine the focus of spatial attention, resulting in enhanced processing of stimuli at early visual-perceptual stages.